The teaching profession: an approach from the continuing education (Olhar de Professor, 2022)
This work approaches the teaching profession from the point of view of continuing education from the perspective of educational praxis, as a reflexive formation. The theme is based on theoretical reflection, based on bibliographic research that permeates the dialogue with classic theorists of contemporary education, especially who present questions on the formation of teacher identity in the relationship with continuing education. In this sense, this text problematizes the discussion of pedagogical training, drawing attention to the valorization of teaching praxis, the initiatives of the subjects (educator and students) and pedagogical know-how, as well as the rescue of the identity of the teaching profession. It also indicates that the continuing training of teachers must be taken over by public policies, as an important strategy at the heart of the teaching profession and the school’s commitment.
Keywords: Teacher training. Continuing education. Teaching praxis. World of work. Professional identity.